Biosynthesis of (R)-3-hydroxybutyric acid from syngas-derived acetate in engineered Escherichia coli. (September 2021) - Fei, Peng; Luo, Yuanchan; Lai, Ningyu; Wu, Hui
Highlights: Engineered E. coli can convert acetate to ( R )-3-hydroxybutyric acid ( R- 3HB). Different hosts of E. coli affected the biosynthesis of R- 3HB. The best strain can produce 0.86 g/L of R- 3HB with a yield of 0.27 g/g. R- 3HB can be produced from syngas-derived acetate with a yield of 0.26 g/g. Abstract: Acetate is a potential non-food carbon source for industrial production, coping with the shortage of food-based feedstocks. ( R )-3-hydroxybutyric acid ( R -3HB) can be used as an important chiral intermediate in the fine chemical and pharmaceutical industry. In this study, the R -3HB biosynthesis pathway was successfully constructed when genes of β-ketothiolase ( phaA ), acetoacetyl-CoA reductase ( phaB ) from Ralstonia eutropha, and propionyl-CoA transferases ( pct ) from Clostridium beijerinckii 8052 were introduced into Escherichia coli. The effects of host E. coli strains, different propionyl-CoA transferases, and post-induction temperatures were investigated. The final concentration of R -3HB reached 0.86 g/L using acetate as the sole carbon source. Subsequently, a kind of culture broth containing the syngas-derived acetate was used to produce 1.02 g/L of R -3HB with a yield of 0.26 g/g. In this study, the engineered E. coli strain could efficiently utilize syngas-derived acetate to synthesize R -3HB.